MITOCHONDRIAL DNA MARKER BASED PHYLOGENETIC ANALYSIS OF PAKISTANI NILGAI (Boselaphus tragocamelus) - G. Abbas; A. Nadeem; M. E. Babar; T. Hussain; N. Aslam; W. Shehzad; M. Tayyab; M. Javed (Journal of Animal and Plant Sciences, 2017)
The Nilgai or Blue Bull (Boselaphus tragocamelus) is the largest Asian antelope which is endemic to Nepal, Pakistan and Indian regions, where these animals are found in packs. Due to rampant hunting, deforestation and habitat degradation, this vulnerable specie is near threatened in many parts of the world. There is need of conservation efforts both at genomic and geographic level. The present study was designed for genomic characterization of Boselaphus tragocamelus in Pakistan by using phylogenetic analysis. Samples from Boselaphus tragocamelus were collected from different parks, zoos and natural habitats. DNA was extracted by standard inorganic extraction method. Primer3 software was used for primer designing targeting Mitochondrial specie identification markers such as d-loop, cytochrome-b and cytochrome-c. After amplification, PCR product was sequenced. Bioinformatics tools were applied for identification of polymorphic loci. Allelic frequency of each locus was calculated. Multidimensional scaling plot illustrated low level of generic diversity among individuals. Phylogenetic analysis revealed conserved neighbouring pattern among different individuals as they shared common ancestry.  This is the first report on genomic characterization of Nilgai from Pakistan. The information of selected species of deer is prerequisite for designing effective strategy in future effective practices for conservation. However further genomic investigations should be carried out at a larger scale.
Keywords: Mitochondrial cytochrome-b; cytochrome-c; d-loop; Phylogenetic; Pakistani nilgai